SPMSM Sliding Mode Control Based on the New Super Twisting Algorithm - Lei Zhang; Jing Bai; Jing Wu (Complexity)
To achieve the high-performance control of the surface-mounted permanent magnet synchronous motor (SPMSM) speed control system, this paper proposes a high-order sliding mode control strategy based on a new super twisting algorithm (NSTA). This strategy introduces an adaptive term in its proportional term based on the original super twisting algorithm, which solves low reaching speed and poor antidisturbance ability due to the square root calculation of proportional term in the original super twisting algorithm. The simulation results show that the proposed strategy can effectively improve the system’s response speed and antidisturbance and greatly suppress the chattering phenomenon of traditional sliding mode control.